1997
DOI: 10.1159/000211502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Percutaneous Absorption of Fluocinolone Acetonide on the Activity of Superoxide Dismutase and Total Antioxidant Status in Patients with Psoriasis

Abstract: This study defines a modification of antioxidant systems by percutaneous absorption of fluocinolone acetonide. Total antioxidant status (TAS) provides an overall indication of antioxidant status. Superoxide dismutase (SOD), a primary antioxidant, accelerates the dismutation of the toxic superoxide radical produced during the oxidative energy processes into the less harmful molecules, hydrogen peroxide and molecular oxygen. We monitored the level of SOD and TAS in 7 males with psoriasis and 6 control subjects b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Several hyperkeratotic syndromes have also been related to altered antioxidant levels in patients' plasma, and both psoriasis and oral leukoplakia have been successfully treated by antioxidant administration. [42][43][44][45][46] The characteristic clinical features of PLS (PPK and periodontitis) are conditions that could be related to, or could be involved in, modification of the critical equilibrium between endogenous ROS production and antioxidant levels or activities. However, data concerning the overall oxidative/antioxidant status of PLS patients are lacking in peerreviewed literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several hyperkeratotic syndromes have also been related to altered antioxidant levels in patients' plasma, and both psoriasis and oral leukoplakia have been successfully treated by antioxidant administration. [42][43][44][45][46] The characteristic clinical features of PLS (PPK and periodontitis) are conditions that could be related to, or could be involved in, modification of the critical equilibrium between endogenous ROS production and antioxidant levels or activities. However, data concerning the overall oxidative/antioxidant status of PLS patients are lacking in peerreviewed literature.…”
Section: Discussionmentioning
confidence: 99%
“…A review of forty-one case–control studies [ 18 58 ] (Table 1 ) has been performed. The number of subjects of the studies ranged from 13 [ 33 ] to 516 [ 41 ]; some studies reported separately data for mild, moderate and severe psoriasis [ 22 , 31 , 32 , 36 , 42 , 45 ], for active and inactive psoriasis [ 46 49 ], for smokers and non smokers [ 20 , 30 ] or for subjects with and without metabolic syndrome [ 55 ]. Therefore fifty-nine case–control comparisons were available from forty-one studies (Table 1 ).…”
Section: Reviewmentioning
confidence: 99%
“…The majority of the case–control comparisons pointed out an increase of markers of peroxidation (88.9 %, 48/54), whereas decreased level of TAC were reported in 63.6 % of the cases (21/33) (Table 1 ). Furthermore, the first study that evaluated TAC in psoriasis reported that TAC in patients with psoriasis was significantly higher compared to healthy controls [ 33 ]. Although, the percentage of case–control comparisons reporting consistent results between peroxidation markers and TAC was 85.7 % (24/28), increased levels of peroxidation markers were accompanied by increased markers of inflammation in 83.3 % (10/12) of the cases, whereas decreased TAC was associated with increased inflammation only in 50 % (3/6) of the cases (Table 1 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This reduction in ROS production could well be a consequence of the inhibiting eect of glucocorticoids on oxidation of metabolites as has been found to occur in lymphocytes. 9,10 Indeed, glucocorticoids increase the plasma level of total antioxidant status in patients 11 and are considered as important hormones for the protection of the body against ROS. 12 The information above led us to investigate the eect of dexamethasone (a synthetic glucocorticoid) on the activity of antioxidant enzymes (superoxide dismutase (SOD), catalase and glutathione peroxidase) of the lymphoid organs (mesenteric lymph nodes (MLN), spleen and thymus).…”
Section: Introductionmentioning
confidence: 99%